2016
DOI: 10.18632/oncotarget.10319
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 enhanced drug sensitivity of human hepatoma cells through glutathione S-transferase pi 1/JNK signaling pathway

Abstract: SIRT3, a class III histone deacetylase, has been implicated in various cancers as a novel therapeutic target. In hepatocellular carcinoma (HCC), we previously reported that SIRT3 induced cell apoptosis by regulating GSK-3β/Bax signaling pathway. Downregulation of SIRT3 in HCC cells facilitates tumor cell survival. In this study, we found that chemotherapeutic agents (doxorubicin, cisplatin and epirubicin) and sorafenib treatment downregulated SIRT3 mRNA and protein levels in three HCC cell lines. MTS assay fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Therefore, it is very important to identify a drug candidate that can replace or be used together with sorafenib. Tao et al have found that upregulation of SIRT3 expression can enhance the sensitivity of HCC cells to chemotherapeutic agents (26). In our study, we found that the upregulation of SIRT3 by transfection in HCC cells reduced cell proliferation and significantly increased sensitivity to sorafenib.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, it is very important to identify a drug candidate that can replace or be used together with sorafenib. Tao et al have found that upregulation of SIRT3 expression can enhance the sensitivity of HCC cells to chemotherapeutic agents (26). In our study, we found that the upregulation of SIRT3 by transfection in HCC cells reduced cell proliferation and significantly increased sensitivity to sorafenib.…”
Section: Discussionsupporting
confidence: 64%
“…Only a recent study highlighted a decreased SIRT-3 expression after the treatment with doxorubicin, cisplatin, and sorafenib in different HCC cell lines, suggesting a regulatory role of the enzyme in the drug sensitivity of HCC cells [62].…”
Section: The Tumor Suppressor Role Of Sirt-3 In Hccmentioning
confidence: 99%
“…e In parallel, proliferation was assessed 48 h later using WST-1 assays. Data from six technical replicates were analyzed and expressed as the mean ± SD cells to chemotherapeutic agents [26]. In our study, we found that the upregulation of SIRT3 by transfection in HCC cells reduced cell proliferation and significantly increased sensitivity to sorafenib.…”
Section: Discussionmentioning
confidence: 70%
“…To date, SIRT3 is known as a tumor suppressor gene [23], and overexpression of SIRT3 reduces cell growth and proliferation in HCC [23,25,26]. SIRT3 also induces apoptosis in abnormal cells through the upregulation of MnSOD, p53, Bax, and Fas [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation